A study of light in a small town - Cotten-Potter, Cory, author; Doenges, Judy, advisor; Altschul, Andrew, committee member; Bernasek, Alexandra, committee member (Colorado State University. Libraries, 2018)
This collection of work contains stories that explore the relationships that individuals have to their familial and cultural pasts. They ask what it means to embrace tradition or eschew heritage, and how to honor family connection or romantic love in a societal landscape that is often under threat. The stories are populated by the surreal and the supernatural, agents that act both with and against these characters as they attempt to articulate to themselves a system for coping with the chaos that surrounds them.